White paper on pandemic preparedness in the blood supply. Issue 1 (25th November 2022) - Strengers, Paul; O'Brien, Sheila F.; Politis, Constantina; Mayr, Wolfgang; Seifried, Erhard; Spencer, Bryan R.
Abstract: Background and Objectives: In March 2020, the WHO declared the SARS‐CoV‐2 corona virus a pandemic which caused a great disruption to global society and had a pronounced effect on the worldwide supply of blood. Materials and Methods: In 2022 an on‐line meeting was organised with experts from Austria, Canada, Germany, Greece, Netherlands and United States to explore the opportunities for increasing preparedness within blood systems for a potential future pandemic with similar, or more devastating, consequences. The main themes included the value of preparedness, current risks to the blood supply, supply chain vulnerabilities, and the role of innovation in increasing resiliency and safety. Results: Seven key recommendations were formulated and including required actions at different levels. Conclusion: Although SARS‐CoV‐2 might be seen as a unique event, global health risks are expected to increase and will affect blood transfusion medicine if no preparedness plans are developed.